A simple macroseismic attenuation model - Lapajne, Janez (Geologija, 1987)
A simple macroseismic attenuation model for an observed intensity I (MSK-78 intensity scale is used) and a “macroseismic" ground acceleration a can be defined by a system of three linear equations of the type I = f (log r) and log a = f (log r), where r is the epicentral distance (which can be a distance from the epicenter to an isoseismal contour in an arbitrary direction, a radius of a circle of equivalent area, or, generally, a distance from the epicenter to any site). Four constants occurring in these equations have understandable physical meanings. Two constants determine the logarithmic degree of attenuation, whereas the two others are characteristic epicentral distances. The model can be easily extended to asymmetrical macroseismic fields by introducing an additional parameter, which is a function of azimuth, and can also be a function of the epicentral distance. In the case of an elliptical field this parameter can be expressed analytically. One extra advantage of the presented model’s equations is that they are dimensionless. An illustration of the use of the model is given for the region of Slovenia (Yugoslavia).